Status and Future Directions of Anti-metastatic Cancer Nanomedicines for the Inhibition of Cathepsin L - Tabish, Tanveer A.; Pranjol, Md Zahidul I.; Whatmore, Jacqueline L.; Zhang, Shaowei (Frontiers in Nanotechnology, 2020)
Angiogenesis, tissue invasion and metastasis in the tumour microenvironment are all critical hallmarks of cancer. Upregulation of cathepsin L plays an important role in angiogenesis and metastasis through its ability to degrade the extracellular matrix, facilitating tissue remodelling and tumour cell invasion. Thus, cathepsin L is a potential therapeutic target for anticancer nanomedicine, with its inhibition emerging as an innovative and potentially promising therapeutic intervention for the development of anti-invasion and anti-metastatic enzyme therapies. Nanotechnology-based platforms have been extensively tested in the anti-cancer nanomedicine field with effective anti-tumour efficacy. These nanodrugs can suppress tumour cell proliferation, thereby reducing tumour growth. Recently, nanomedicinal approaches have also emerged as effective anti-metastatic strategies, including the use of graphene oxide and gold nanoparticles. With a focus on recent advances in developing nanotechnology to inhibit cathepsin L, this review provides an in-depth examination of this stimulating field in the context of tumour microenvironments. Innovative anti-metastatic agents may lead to new options for the treatment of cancers.